The intertwining of Zn-finger motifs and abiotic stress tolerance in plants: Current status and future prospects - Moulick, Debojyoti; Bhutia, Karma Landup; Sarkar, Sukamal; Roy, Anirban; Mishra, Udit Nandan; Pramanick, Biswajit; Maitra, Sagar; Shankar, Tanmoy; Hazra, Swati; Skalicky, Milan; Brestic, Marian; Barek, Viliam; et al. (Frontiers in Plant Science, 2023)
Environmental stresses such as drought, high salinity, and low temperature can adversely modulate the responses of field crops by altering the morphological, physiological, and bio-chemical processes in plants. It is estimated that about 50% of global crop productivity is limited due to various kinds of abiotic stresses. However, there are two ways by which plants can survive these abiotic stresses; a) through management practices, and b) through adaptive mechanisms to tolerate stresses. The adaptive mechanisms of tolerant plants are mostly linked to the signalling transduction pathways, triggering the action of plant transcription factors and controlling the expression of various stress-regulated genes. In recent times, many studies have elucidated the significant roles of Zn finger motifs during the abiotic stress responses in plants. A wide range of Zn-binding motifs has been recognized and grouped under the Zn finger protein (ZFP) families. The common structure of the proteins was reported to include a repeated Zn-binding motif comprising of highly conserved sequence of cysteine (Cys) and histidine (His) residues. The proteins exhibit a unique tetrahedral coordination geometry where Zn2+ ion is attached to the amino acid residues. The current review has summarized the structures, types, and functions of various ZFPs along with a thorough insight into their mechanisms of action in during various abiotic stress responses in plants including several important crops such as rice, wheat, maize, sorghum, soybean, tomato, cucumber, etc. This concise but comprehensive study will pave the way for future research further explore the potential roles of ZFPs and their biotechnological applications in combat-ing various stresses induced on crops due to climate change.